46‐1: Patterned Glass Diffuser (PGD) for MiniLED Backlights. Issue 1 (28th June 2021) - Mi, Xiang-Dong; Wu, Jen-Chieh; Sun, Hai-Wei; Chen, Ming; Varanytsia, Andrii; Han, Songfeng; Allen, Kirk R; Maurey, Pamela A; Baker, David L; Tokar, Josh; Ouyang, Michael X; Niu, Tzu-Ling; et al.
Abstract : We report on a monitor‐sized, thin, dimensionally and thermally stable mini‐LED backlight enabled by a patterned glass diffuser (PGD). Our backlight has a luminance of between 0.9 × and 1.05 × compared to a reference mini‐LED backlight using a thick diffuser plate, while providing a better local dimming control and comparable zone and panel luminance uniformity and color uniformity. The PGD technology can reduce the number of LEDs.